2022
DOI: 10.1016/j.jcf.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

TLR5 signalling is hyper-responsive in porcine cystic fibrosis airways epithelium

Abstract: Excessive lung inflammation and airway epithelium damage are hallmarks of cystic fibrosis (CF) disease. It is unclear whether lung inflammation is related to an intrinsic defect in the immune response or to chronic infection. We aimed to determine whether TLR5-mediated response is defective in the CF airway epithelium. We used a newborn CF pig model to study intrinsic alterations in CF airway epithelium innate immune response. Airway epithelial cells (AECs) were stimulated with flagellin or lipopolysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…This increase in TMPRSS2 expression was more notable in Calu-3-CFTR-KD than in Calu-3-CFTR-WT (Figure 2B), and the TMPRSS2 upregulation was also detected at the protein level (Figure 2D). As expected, flagellin induced the synthesis of the proinflammatory cytokines interleukin (IL)-8 and IL-6 (Supplementary Figure 2A, B) both in Calu-3-CFTR-WT and Calu-3-CFTR-KD cells, and this inflammatory response was relatively higher in the Calu-3-CFTR-KD cells, which agrees with previous work showing that CF epithelial cells from human (19) or porcine (20) origin exhibit an enhanced inflammatory response to flagellin.…”
Section: Ace2 Furin and Tmprss2 Expression In Cf And Non-cf Primary Human Aecs Upon P Aeruginosa Infectionsupporting
confidence: 92%
“…This increase in TMPRSS2 expression was more notable in Calu-3-CFTR-KD than in Calu-3-CFTR-WT (Figure 2B), and the TMPRSS2 upregulation was also detected at the protein level (Figure 2D). As expected, flagellin induced the synthesis of the proinflammatory cytokines interleukin (IL)-8 and IL-6 (Supplementary Figure 2A, B) both in Calu-3-CFTR-WT and Calu-3-CFTR-KD cells, and this inflammatory response was relatively higher in the Calu-3-CFTR-KD cells, which agrees with previous work showing that CF epithelial cells from human (19) or porcine (20) origin exhibit an enhanced inflammatory response to flagellin.…”
Section: Ace2 Furin and Tmprss2 Expression In Cf And Non-cf Primary Human Aecs Upon P Aeruginosa Infectionsupporting
confidence: 92%
“…Indeed, CFTR belongs to a protein-protein interactions (PPI) network (Pereira et al, 2021; Farinha and Gentzsch, 2021), and the absence of CFTR may perturb its direct or indirect interactors, and propagate dysregulations towards various biological pathways in which these interactors play a role. In agreement with this idea, studies on CFTR -/- knockout mice (Crites et al, 2015), CFTR -/- knockout piglets (Fleurot et al, 2022), and cell lines in which CFTR is inactivated by the CRISPR/Cas9 technology (Hao et al, 2020) have reported that the absence of CFTR affects cell signalling and transcriptional regulation. These dysregulations may explain various and apparently unrelated cellular phenotypes, including uncontrolled pro-inflammatory response (Jacquot et al, 2008), unbalanced oxidative stress with increased reactive oxygen species (Jeanson et al, 2012), impaired epithelial regeneration (Conese and Di Gioia, 2021), or perturbation of cell junctions and cytoskeleton (Pankonien et al, 2022).…”
Section: Introductionmentioning
confidence: 76%
“…NTRK3 [81], MMP9 [82], IGF2 [83], SOCS3 [84], IGFBP2 [85], SLC1A3 [86], NOS1AP [87], HP (haptoglobin) [88], TLR5 [89], ARG1 [90], NRG1 [91], RGS5 [92], LCN2 [93], TSPO (translocator protein) [94], PLAU (plasminogen activator, urokinase) [95], MME (membrane metalloendopeptidase) [96], BST1 [97], NR6A1 [98], TLR4 [99], NRN1 [100], ABCA13 [101], CTSD (cathepsin D) [102], NCAM1 [103], SIGMAR1 [104], CNR2 [105], CCR4 [106], ABCB1 [107], TIMELESS (timeless circadian regulator) [108], IRF8 [109], TXNIP (thioredoxin interacting protein) [110], SUV39H1 [111], CRY1 [112], CRY2 [113], PDCD4 [114] and MGAT5 [115] played an important role in depression and anxiety. Accumulating evidence has demonstrated that MMP9 [116], S100A12 [117], HP (haptoglobin) [118], TLR5 [119], NRG1 [120], PLAU (plasminogen activator, urokinase) [121], SLC11A1 [122], AQP9 [123], CHIT1 [124], TLR4 [125], SLC26A8 [126], CTSD (cathepsin D) [127], SERPINB1 [128], FASLG (Fas ligand) [129], SLC4A4 [130], AQP3 [131] and IRF8 [132] appears to be constitutively associated with CF . MMP9 [133], S100A12 [134], SOCS3 [135], MMP8 [136], CRISP3 [137], S100A9 [138], RETN (resistin) [139], IL1RN [140], TLR4 [141], GGT1 [142], CTSD (cathepsin D) [143], FASLG (Fas ligand) [144], CCR4 [145], FCRL3 [146] and ABCF1 [147] were revealed and regarded as diagnostic biomarker in pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…CHGA (chromogranin A) [48] and IL23R [49] [99], NRN1 [100], ABCA13 [101], CTSD (cathepsin D) [102], NCAM1 [103], SIGMAR1 [104], CNR2 [105], CCR4 [106], ABCB1 [107], TIMELESS (timeless circadian regulator) [108], IRF8 [109], TXNIP (thioredoxin interacting protein) [110], SUV39H1 [111], CRY1 [112], CRY2 [113], PDCD4 [114] and MGAT5 [115] played an important role in depression and anxiety. Accumulating evidence has demonstrated that MMP9 [116], S100A12 [117], HP (haptoglobin) [118], TLR5 [119], NRG1 [120], PLAU (plasminogen activator, urokinase) [121], SLC11A1 [122], AQP9 [123], CHIT1 [124], TLR4 [125], SLC26A8 [126], CTSD (cathepsin D) [127], SERPINB1 [128], FASLG (Fas ligand) [129], SLC4A4 [130], AQP3 [131] and IRF8 [132] appears to be constitutively associated with CF. MMP9 [133], S100A12 [134], SOCS3 [135], MMP8 [136], CRISP3 [137], S100A9 [138], RETN (resistin) [139], IL1RN [140], TLR4 [141], GGT1 [142], CTSD (cathepsin D) [143], FASLG (Fas ligand) [144], CCR4 [145], FCRL3 [146] and ABCF1 [147] were revealed and regarded as diagnostic biomarker in pancreatitis.…”
Section: Discussionmentioning
confidence: 99%